"Be My Guest": The Link Between Concentrated Poverty, Race, and Family-Level Support. (August 2018) - Whitehead, Ellen M.
Exposure to concentrated poverty is largely understood as reflecting the role of individual influences and racial disparities, with less information on the role of extended family. Coresiding with family members represents one classic mechanism reducing exposure to economic hardship, but we often combine those residing as "guests" with those who are "hosting" their extended family. Using data from the Fragile Families and Child Wellbeing Study ( N = 4, 054), I explore the impact of living with family on the likelihood of residing in concentrated poverty. I find that mothers who coreside as "guests" with family, but not those who are hosting their relatives, have significantly lower odds of living in impoverished neighborhoods compared with those who do not reside with relatives, once controlling for socioeconomic and demographic characteristics. This research reveals that family networks do play a role in structuring neighborhood attainment, with strong implications for better understanding vulnerability to neighborhood poverty.